Subcellular localization of transglutaminase. Effect of collagen. - Juprelle-Soret, M (1988)
1. The subcellular distribution of transglutaminase was investigated by using the analytical approach of differential and isopycnic centrifugation as applied to three organs of the rat: liver, kidney and lung. After differential centrifugation by the method of de Duve, Pressman, Gianetto, Wattiaux & Appelmans [(1955) Biochem. J. 63, 604-617], transglutaminase is mostly recovered in the unsedimentable fraction S and the nuclear fraction N. After isopycnic centrifugation of the N fraction in a sucrose density gradient, a high proportion of the enzyme remains at the top of the gradient; a second but minor peak of activity is present in high-density regions, where a small proportion of 5'-nucleotidase, a plasma-membrane marker, is present together with a large proportion of collagen recovered in that fraction. 2. Fractions where a peak of transglutaminase was apparent in the sucrose gradient were examined by electron microscopy. The main components are large membrane sheets with extracellular matrix and free collagen fibers. 3. As these results seem to indicate that some correlation exists between particulate transglutaminase distribution and those of collagen and plasma membranes, the possible binding of transglutaminase by collagen (type I) and by purified rat liver plasma membrane was investigated. 4. The binding studies indicated that collagen is able to bind transglutaminase and to make complexes with plasma-membrane fragments whose density is higher than that of plasma-membrane fragments alone. Transglutaminase cannot be removed from such complexes by 1% Triton X-100, but can be to a relatively large extent by 0.5 M-KCl and by 50% (w/v) glycerol. 5. Such results suggest that the apparent association of transglutaminase with plasma membrane originates from binding in vitro of the cytosolic enzyme to plasma membrane bound to collagen, which takes place during homogenization of the tissue, when the soluble enzyme and extracellular components are brought together.